Foreword - Sauerland, Uli; Solt, Stephanie (Proceedings of Sinn und Bedeutung, 2019)
In these volumes, we are very pleased to present a collection of papers based on talks and posters at Sinn und Bedeutung 22, which took place in Berlin and Potsdam on September 7-10, 2017, jointly organized by the Leibniz-Centre for General Linguistics (ZAS) and the University of Potsdam. SuB22 received 183 submitted abstracts. Out of these, the organizing committee selected 39 oral presentations in the main session, 4 oral presentations in the special session ‘Semantics and Natural Logic’, and 24 poster presentations. There were an additional 6 invited talks. In total, 58 of these contributions appear in paper form in the present volumes. We would like to take this opportunity to thank the many colleagues who helped to make SuB22 a success: our fellow organizers Guillermo Del Pinal, Mira Grubic, Manfred Krifka and Malte Zimmermann, without whom the conference would not have been possible; the nearly 200 reviewers from around the world; our invited speakers Márta Abrusán, Amy Rose Deal, Danny Fox, Hannes Leitgeb, Louise McNally and Philippe Schlenker; staff members Anja Gollrad, Ines Mauer and Azura Frömming, who dealt with countless practical details; our student assistants Carla Boos, János Litzinger, Norman Brackmann, Marius Küch and Henry Salfner, who ably supported us in the preparation phases and during the conference, as well as Meredith Alongi, Jordan Chark and Elizabeth Pankratz, who served as editorial assistants in the production of these proceedings; and of course the presenters, session chairs and audience members. We would also like to acknowledge financial support from the Deutsche Forschungsgemeinschaft (grant KR 951/13-1), the Leibniz-Centre for General Linguistics, and the University of Potsdam, as well as surplus funds from SuB21 from the University of Edinburgh. We look forward to seeing everyone in September 2018 in Barcelona for SuB23! Berlin, July 2018 Uli Sauerland and Stephanie Solt